The receptor VLDLR binds Eastern Equine Encephalitis virus through multiple distinct modes - Cao, Duanfang; Ma, Bingting; Cao, Ziyi; Xu, Xiaoyu; Zhang, Xinzheng; Xiang, Ye (Nature communications, 2024)
Eastern Equine Encephalitis virus (EEEV) is an alphavirus that can cause severe diseases in infected humans. The very low-density lipoprotein receptor (VLDLR) was recently identified as a receptor of EEEV. Herein, we performed cryo-electron microscopy structural and biochemistry studies on the specific interactions between EEEV and VLDLR. Our results show that VLDLR binds EEEV at three different sites A, B and C through its membrane-distal LDLR class A (LA) repeats. Site A is located in the cleft in between the E1-E2 heterodimers. Site B is located near the connecting β ribbon of E2 and is in proximity to site A, while site C is on the domain B of E2. The binding of VLDLR LAs to EEEV is in complex modes, including the LA1-2 and LA3-5 mediated two major modes. Disruption of the LA1-2 mediated binding significantly affect the cell attachment of EEEV. However, the mutation W132G of VLDLR impairs the binding of LA3, drives the switch of the binding modes, and significantly enhances the attachment of EEEV to the cell. The W132G variant of VLDLR could be identified in human genome and SNP sequences, implying that people with similar mutations in VLDLR may be highly susceptible to EEEV infection. Eastern equine encephalitis virus (EEEV) uses the very low-density lipoprotein receptor (VLDLR) to infect cells of different species. This study finds that the ecto LA repeats of VLDLR binds EEEV at three distinct sites, generating multiple different binding modes that facilitate the cross-species transmission of EEEV.